Predictive value of a 24 hour tuberculin skin test evaluation. Issue 5 (1st May 1997) - Öztürk, Fadıl; Eskiocak, Muzaffer; Bay, Ali; Sancak, Recep; Dabak, Şennur; Gürses, Nuran
Abstract : The predictive value of induration 24 hours after administration of purified protein derivative (PPD) was examined. Altogether 1082 healthy schoolchildren were tested using 5 tuberculin units of PPD. Induration was measured at 24, 48, and 72 hours. At 24 hours, induration of any size had a relatively low positive predictive value (63%), although indurations >5 mm had a higher (86%) positive predictive value.